Analisis Syair Lagu Kidung Jemaat No 26 “Mampirlah Dengar Doaku” di Gereja GKPI Harian Boho Ressort Sagala Samosir - Mia Laurent Manalu; Lince R.T Simamora; Tahado Waruwu (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to determine the analysis of the lyrics of the hymn of the congregation No. 26 Mampirlah Dengar Doaku by analyzing the meanings contained in each lyric of the song. This study uses qualitative research methods including data collection, data reduction, data presentation, and data verification. And all observations and methods carried out by the author during the research, the results of the analysis show that with the song Mampirlah Dengar Doaku, the analysis of this song can help us understand more deeply about our relationship with God and how we can develop that relationship. Recognizing God's presence: This song reminds us of God's presence in our lives and how we can feel His presence, Expressing feelings, the analysis of this song can help us express our feelings about the difficulties and suffering we experience. From this study, the author hopes to understand the meaning of the songs sung in worship, so that an interpretation is created when singing songs, and the congregation not only sings but can live the song